The cabin at the end of the world : a novel - Tremblay, Paul (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2018)
"The Bram Stoker Award-winning author of A Head Full of Ghosts gives a new twist to the home invasion horror story in a heart-palpitating novel of psychological suspense that recalls Stephen King's Misery, Ruth Ware's In a Dark, Dark Wood, and Jack Ketchum's cult hit The Girl Next Door"--
A seven-year-old girl and her fathers are confronted by four menacing strangers while vacationing at a remote New Hampshire cabin.
Keywords: Home invasion -- Fiction; Murder -- Fiction; Visions -- Fiction; Paranormal fiction; Thrillers (Fiction).; Psychological fiction; Suspense fiction; Psychological fiction